Ultrastructural Studies on Blood Brain Barrier in Hypothalamus of Indian Buffalo - Pathak, Devendra; Bansal, Neelam (Indian Journal of Veterinary Anatomy, 2015)
The present study was conducted on hypothalami of six adult buffaloes. The tissues were processed for transmission electron microscopic study. The blood brain barrier was found scattered in between the neuronal elements of different nuclei of hypothalamus of buffaloes. The blood brain barrier was composed of hypothalamic blood capillary endothelial cells, end feet of astrocytes and pericytes. The squamous endothelial cells and neighboring endothelial cells of blood capillaries were joined together by tight junction like contacts thus dividing the membranes into two distinct sides viz: blood side or luminal side and adluminal side or brain side. There were no inter cellular clefts and fenestrations were observed in the present study. Cytoplasm of endothelial cells showed a large number of mitochondria. Foot process of astrocytes was intimately associated with the endothelial cells. Pericyte was embedded in the basement membrane of blood brain barrier at places.